Effect of ribavirin on hepatitis A virus replication in vitro - Chaudhary, Rabindra K (Pulsus Group Inc, 1992)
The effect of ribavirin on fetal Rhesus monkey kidney cells (FRhK-4) acutely or chronically infected with hepatitis A virus was studied. The effect of ribavirin on hepatitis A virus yield as detected by radioimmunoassay in acutely infected FRhK-4 cells was dependent on hepatitis A virus inoculum dose. Treatment with 100 μg/mL ribavirin completely inhibited hepatitis A virus growth in cultures infected with 100 to 800 tissue culture infectious dose 50 (TCID(50)) hepatitis A virus, but inocula of 800 to 1600 TCID(50) resulted in limited production of virus. The effect was time dependent and required more than 96 h of treatment to inhibit the virus completely. Ribavirin was less effective in treating cells persistently infected with hepatitis A virus, although there was significant inhibition of hepatitis A virus (82%) in persistently infected cells as well. Ribavirin had some inhibitory effect on cell growth; treatment with 25, 50 or 100 μg/mL ribavirin reduced cell growth by approximately 0, 20 and 40%, respectively.